Vacuum System for Reinforcing Fabric Handling - Kužel, Jan; Růžek, Roman (Manufacturing Technology Journal, 2022)
The paper considers questions asotiated with automated systems to produce composite parts. Exist-ing automated systems used in aerospace production are usually based on lay-up technologies. The main objective of the on-going development is to find an affordable production technology for com-posite parts that can be easily automated. The handling with dry reinforcing fabrics is objective of the paper: dry fabric is placed in a suitable mold where it is impregnated by selected type of a matrix and consolidated under vacuum bag afterwards. Based on experiments using standard gripping systems, it was found that local damage of reinforcing fibers occurs. For these reasons, a new vacuum suction-based gripper was developed. As a suction source industrial vacuum cleaner was used, whose perfor-mance can be regulated continuously. Functionality of the suction system was verified on six differ-ent types of reinforcing materials, using two different types of suction grid at three different levels of vacuum cleaner performance. Performed experiments verified suitability of the designed solution for manipulation with dry fabrics without the risk of their damage.
Keywords: Fibre reinforced plastic; Vacuum System; Automated Production; Gripper; Handling